An estimation of greenhouse gas emission from livestock in Bangladesh - Das, Nani Gopal; Sarker, Nathu Ram; Haque, Md Najmul (Journal of Advanced Veterinary and Animal Research, 2020)
Objectives: The study was undertaken to investigate the greenhouse gas (GHG) emission from livestock in Bangladesh. Materials and Methods: The GHG emission inventory of livestock in Bangladesh was estimated according to the tier 1 approach of the Intergovernmental Panel on Climate Change (IPCC) using livestock population data from 2005 to 2018. It was also extrapolated for the next three decades, according to the growth of the livestock population. Results: According to the calculation, the GHG emission from livestock was 66,586 Gg/year CO2 equivalent (CO2e) in 2018. This emission may rise to 69,869, 80,618, 94,638, and 113,098 Gg/ year CO2e in 2020, 2030, 2040, and 2050, respectively. The share of enteric methane, manure methane, direct nitrous oxide emission, and indirect nitrous oxide emission in the total GHG emissions represented 44.0%, 3.6%, 51.5%, and 0.9%, respectively, in 2018. It may arise at a rate of 1.54%–1.74% annually until 2050. Conclusion: The GHG inventory may guide professionals to formulate and undertake the effective mitigation measures of GHG emissions from livestock in Bangladesh. However, this inventory can be amended following the tier 2 approach recommended by the IPCC if necessary data are available at the national level. J. Adv. Vet. Anim. Res., 7(1): 133-140, March 2020